The effects of secondary filler on the impact behaviour of hybrid polymer composites / Anizah Kalam - Kalam, Anizah; Nor Berhan, Mohamad; Wahab, Noraini; Abdul Razak, Noorrul Wahida (Research Management Institute (RMI), 2012)
Oil Palm fruit bunch fibre (OPFB) derived from empty fruit bunch (EFB) that are abundantly available in Malaysia as oil palm mill waste, is worthy to explore its capability as filler in composites. Previous work [1-2] showed that the addition of PPnanoclay into OPFB/PP composites has improved its tensile modulus, flexural properties and impact strength. The study has also found out that the combination of clay and coarser OPFB particles (250 m) indicated more properties improvement [2]. Thus this study will further investigate the effect of clay as secondary fillers on the impact behaviour of OPFB/PPnanoclay/PP hybrid composites at various PPnanoclay loading and OPFB size of greater than 250 m (however less than 500 m within the capability of available injection moulding). The optimum PPnanoclay loading and OPFB size will be investigated for those composites. Thereby, hybrid composites consisted of oil palm fruit bunch (OPFB) fibre, polypropylene-clay (PPnanoclay) nanocomposite and pure polypropylene at various PPnanoclay loading and OPFB size will be compounded by using thermal mixer. The test samples will be prepared by using injection moulding machines. The composite samples will be characterized according to ASTM standard for tensile, flexural and impact tests. Fracture surface observation will also be conducted to have further understanding on the role of secondary filler in hybrid composites. Some basic mechanical properties and the impact strength of the composites will be obtained to complement the existing data or information on OPFB filled polymer composites. The information is expected to be useful in promoting OPFB as natural filler in polymer composites especially for automotive application